Usefulness of the Tidal Model concepts to the care of adolescents deprived of liberty - Alana Costa Silva; Rutherford Alves Moura; Dayanne Rakelly de Oliveira; Edilma Gomes Rocha Cavalcante; Álissan Karine Lima Martins; Grayce Alencar Albuquerque; José Wicto Pereira Borges (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To reflect on the usefulness of the concepts of the Tidal Model in nursing care for adolescents deprived of liberty. Method: Critical reflection of the theory, according to the evaluation proposed by Meleis, focusing on the usefulness of the theory, based on the practice criterion, according to the unit of analysis applicability of the theory. Results: The Tidal Model is composed of concepts that allow the understanding of the context in which the adolescent deprived of liberty is inserted and prepare nurses for the operationalization of their clinical practice aimed at this adolescent, enabling the professional to observe its limits, such as issues related to social reintegration, which requires intersectoral partnerships, and the need for anchoring in other theories. Final considerations: The concepts of the Tidal Model are useful and can be applied to the nursing care provided to adolescents in situation of deprivation of liberty, promoting the centrality of care for this adolescent.